Site-specific His/Asp phosphoproteomic analysis of prokaryotes reveals putative targets for drug resistance - Shu-Jung Lai (BMC Microbiology, 2017)
Abstract Background Phosphorylation of amino acid residues on proteins is an important and common post-translational modification in both eukaryotes and prokaryotes. Most research work has been focused on phosphorylation of serine, threonine or tyrosine residues, whereas phosphorylation of other amino acids are significantly less clear due to the controversy on their stability under standard bioanalytical conditions. Results Here we applied a shotgun strategy to analyze the histidine and aspartate phosphorylations in different microbes. Our results collectively indicate that histidine and aspartate phosphorylations frequently occur also in proteins that are not part of the two-component systems. Noticeably, a number of the modified proteins are pathogenesis-related or essential for survival in host. These include the zinc ion periplasmic transporter ZnuA in Acinetobacter baumannii SK17, the multidrug and toxic compound extrusion (MATE) channel YeeO in Klebsiella pneumoniae NTUH-K2044, branched amino acid transporter AzlC in Vibrio vulnificus and the RNA-modifying pseudouridine synthase in Helicobacter pylori. Conclusions In summary, histidine and aspartate phosphorylation is likely to be ubiquitous and to take place in proteins of various functions. This work also sheds light into how these functionally important proteins and potential drug targets might be regulated at a post-translational level.